Barriers to community capacity building for tourism development in communities in Shiraz, Iran - Aref, Fariborz (Routledge, 2011)
This paper illustrates barriers to community capacity building (CCB) in tourism development, based on a questionnaire survey of 175 community leaders carried out in the city of Shiraz in Iran. It builds on the work of other researchers who found that in developing countries, a lack of CCB is an influential barrier to tourism development. The study found that the main barriers to CCB are to be found at the organizational and community levels. The barriers did not manifest equally in every community and tend to exhibit higher intensity and greater persistence in the new district in comparison to the old historic district of Shiraz. Community members have restricted access to decision-making, a lack of resources, knowledge, skills and education and lack a sense of ownership with regard to tourism. The centralization of government is a further problem. This paper shows that concerned leaders, especially those involved in tourism industry, could utilize the results of this study in their efforts to resolve the barriers to tourism development in their communities.